BLANCHE DAN STANLEY, DUA ALTER-EGO TENNESSEE WILLIAMS DALAM A STREETCAR NAMED DESIRE: *) SEBUAH TINJAUAN PSIKOANALISIS - Iswalono, Sugi; Nurhayati, Ari; Anggraeni, Niken (Diksi, 2008)
This article is about a research aimed at finding the forms of Williams'desire which is unfulfilled or repressed into his unconscious mind as sublimated inhis play, A Streetcar Named Desire. In other words, Williams' main inventedcharacters, Blanche and Stanley, whose personalities are shaky or chaotic,represent the expression of the playwright's unbalanced personality which issublimated in the play.The research is conducted by tracing Williams' life and understanding theplay A Streetcar Named Desire as well as the criticism on it and his other works ofwhich the aspects are comparable. To come to the desired aim, psychoanalyticcriticism is aptly opted to expose the issue. In relation to the various schools ofpsychoanalysis, the research applies Freud's psychoanalytic perspective, focusingon the relationship between the author and his work.The research results show the following. Firstly, A Streetcar NamedDesire was written on the basis of Williams' life, especially his childhood andyouth, in which he experienced unhappy and inharmonious relationship with hisfather and, as a consequence, it made his personality chaotic or unbalanced, whichthen brought about sexual perversion in him, making him a passive homosexual.Secondly, the perverted sexual behavior of his was as a matter of fact themanifestation of his rebellion against his father, which he then expressed throughhis work. Thirdly, such behavior was inappropriate in the American cultural andsocial life during his life span and, therefore, he had to repress his desire because itwas impossible for him to release his libidinous drive so that, to avoid neurosis, hesublimated it in literature. In other words, A Streetcar Named Desire is thesublimation of Williams' repressed libido to express his rebellion against his fatherand to release his libidinous drive. In that case, he creates Stanley and Blanche ashis fantasy to escape from his repression though only a minute's escape.Key words: Tennessee Williams, childhood, chaotic personality, libido, father,repression, neurosis, sublimation, Blanche, Stanley